Analisis Pengaruh Kualitas Pelayanan Kepolisian Terhadap Kepuasan Masyarakat di Polres Pegunungan Bintang - Cakradini, Rudy; Sibarani, Mentiana (Indo-MathEdu Intellectuals Journal, 2025)
The quality of police services is a crucial factor in building public trust in law enforcement institutions. The Pegunungan Bintang District Police (Polres Pegunungan Bintang), as a public service institution in a border area, faces unique challenges in delivering excellent service to the community. This study aims to determine the level of public satisfaction with police services at Polres Pegunungan Bintang. A quantitative approach is employed, with data collected through questionnaires distributed to community members who have received police services. The collected data will be analyzed to measure and evaluate the quality of services provided. The SERVQUAL method, which consists of five dimensions tangibles, reliability, responsiveness, assurance, and empathy will be used as a framework for evaluating service quality and will be further elaborated once the data on public satisfaction is obtained. The data analysis used in this research is multiple linear regression. The results of this study are expected to provide input for Polres Pegunungan Bintang in formulating strategies for continuous improvement in public service quality.